Health Status of Spiny Lobster Panulirus homarus with Sub-Mersible Net Cage System in the Different Depths at Kepulauan Seribu, DKI Jakarta - Dinamella Wahjuningrum; Irzal Effendi; Yani Hadiroseyani; Tatag Budiardi; Iis Diatin; Mia Setiawati; Yuni Puji Hastuti; Agus Oman Sudrajat; Yonvitner; Sri Nuryati; Putri Utami (Jurnal Akuakultur Indonesia)
ABSTRACT